Physical and mechanical properties keramsite obtained with added glauconite - Franus, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
This paper presents the assessment of the physical and mechanical properties lightweight of aggregate obtained from the addition of expanded clay mineral clay – glauconite and clay from the bed, “Buda Mszczonowska”. Crushed plastic was prepared by firing at a temperature of over 1170 ° C. Evaluation of physical parameters was based on parameters such as density, bulk density and bulk density, tightness, porosity, water absorption. The study of mechanical properties was carried out on the basis of aggregate hardiness, resistance to crushing, abrasion in the drum Los Angeles. In addition, the compounds were determined in the aggregate coloring. Use glauconite in the lightweight of aggregate is beneficial for the texture of the sinter resulting in the formation of a glassy layer on the surface of the granules, and by increasing their porosity. Investigated the properties indicate that the resulting lightweight of aggregate with glauconite meets the basic requirements for materials used in construction.